The protégé : a novel - Gehrman, Jody (Crooked Lane, 2023)
"Dr. Hannah Bryers, anthropology professor and forensics expert at the prestigious Mad River University, takes pleasure in examining corpses, but small talk and living people fill her with dread. When she's not teaching, she analyzes the decomposing flesh of murder victims around the globe. Winter Jones is Hannah's most promising graduate student. She's smart, cunning, and dedicated, but she's got her own agenda for coming to Mad River: to bring Hannah Bryers down"--